1994
DOI: 10.1007/s002800050190
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of tissue disposition of cis-ammine/cyclohexylamine-dichloroplatinum(II) and cisplatin in mice bearing FSaIIC tumors

Abstract: The clinical potential of mixed amine platinum(IV) complexes has been identified, and interest in this new class of antitumor agents has been heightened by demonstration of their activity in cisplatin-resistant neoplasms. These tetravalent platinum agents are expected to undergo a reductive reaction to form the corresponding platinum(II) drug prior to eliciting biological activity. cis-Ammine/cyclohexylamine-dichloroplatinum(II) is one such product that we evaluated with cisplatin in vivo, and we found the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has previously been suggested that precipitation of plasma proteins with cold ethanol may be a good alternative to the ultrafiltration of plasma for measurement of unbound platinum [13,18]. In addition, trichloroacetic acid (TCA) has been used to measure unbound platinum [8,21,22,25]. Herein we report on experiments in which the ethanol precipitation method was validated and compared with the results obtained with two ultrafiltration systems and the TCA precipitation method.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been suggested that precipitation of plasma proteins with cold ethanol may be a good alternative to the ultrafiltration of plasma for measurement of unbound platinum [13,18]. In addition, trichloroacetic acid (TCA) has been used to measure unbound platinum [8,21,22,25]. Herein we report on experiments in which the ethanol precipitation method was validated and compared with the results obtained with two ultrafiltration systems and the TCA precipitation method.…”
Section: Introductionmentioning
confidence: 99%